Identification and classification of effective factors on realization of entrepreneur government through application of fuzzy TOPSIS - Vahideh Bamshad (Management Science Letters)
Entrepreneurship is considered as the key factor of economic growth and development in modern day. Entrepreneurship takes place either individually or organizationally and they normally undertake the risk of entrepreneurship. Entrepreneurs experience the most severe conditions when they deal with a government, which is completely unfamiliar with some rules. If a government supports an entrepreneur one with the required characteristics, then entrepreneurship is facilitated largely for both individuals and organizations. This article provides definitions, features and the effective factors on realization of an entrepreneur government with respect to significance of such a government. To this end, a list of factors that may lead to realization of entrepreneur government was derived from previous studies and then the fuzzy TOPSIS method and collected opinions of experts were applied to facilitate the determination of each of these factors. Finally, a list of influential factors was presented with regards to effective factors on realization of entrepreneur government.